Examining factors associated with unprotected sexual behavior among Black Americans postrelease from incarceration in New York City - Rowell-Cunsolo, Tawandra L. (J Offender Rehabil, 2018)
Black Americans are overrepresented among incarcerated individuals and those infected with sexually transmitted infections. We assessed unprotected sexual behavior among 165 formerly incarcerated Black Americans in New York City, New York. Most participants (63%) reported engaging in unprotected sexual behavior post-incarceration. According to our regression results, less time spent in jail and reporting multiple sexual partnerships were associated with a greater likelihood of engaging in unprotected sexual behavior. High rates of unprotected sexual behavior may place formerly incarcerated Black Americans at risk for sexually transmitted infections. Discharge planning programs that include STI/HIV prevention information and education may be useful for this population.